Distribusi Zakat Sektor Perbaikan Kesejahteraan Masyarakat: Analisis Indeks Pembangunan Manusia di Pulau Jawa pada Tahun 2019-2024 - Aimatus Solehah; Fery Maulana Malik; Encik Dalilah Jasmine (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the effect of sectoral zakat fund distribution on community welfare as represented by the Human Development Index (HDI) in six provinces on the island of Java, namely DKI Jakarta, West Java, Banten, Central Java, DI Yogyakarta, and East Java during the period 2021–2024. The method used is a quantitative approach utilizing secondary data. The data was obtained from annual reports related to the distribution of zakat funds in the economic, education, and health sectors for the period 2019–2024, sourced from the National Zakat Management Report, PPID BAZNAS, and HDI data from the Central Statistics Agency (BPS). The results show that the distribution of zakat funds in the education and health sectors has a significant effect on increasing the HDI in the research area. This finding confirms that zakat plays a strategic role in promoting community welfare through improvements in the quality of education and health services. However, zakat distributed in the economic sector has not had a significant impact on increasing the HDI, so it is necessary to optimize the management and empowerment of economic zakat so that it can contribute more to human development in the future.